2017
DOI: 10.1104/pp.17.00390
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between Reproductive and Immune Pistil Transcriptomes of Arabidopsis Species

Abstract: ORCID IDs: 0000-0002-9468-6335 (M.M.-P.); 0000-0001-6442-4302 (T.D.).Independent lines of evidence suggest that members from ancient and polymorphic gene families such as defensins and receptor-like kinases mediate intercellular communication during both the immune response and reproduction. Here, we report a large-scale analysis to investigate the extent of overlap between these processes by comparing differentially expressed genes (DEGs) in the pistil transcriptomes of Arabidopsis thaliana and Arabidopsis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 75 publications
2
26
0
Order By: Relevance
“…As a control, pistils collected 24 h after emasculation, but otherwise untreated, were used for comparison with infected pistils. The surface of infected pistils and leaves collected 3 days after infection (3 DAI) showed profuse hyphal growth in A. lyrata (Additional file 8 : Figure S3) as well as in A. thaliana and A. halleri [ 20 ]. For both control and treatments, pistils or leaves from three biological replicates were collected, each replicate containing equivalent amounts of material from 4 individual plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a control, pistils collected 24 h after emasculation, but otherwise untreated, were used for comparison with infected pistils. The surface of infected pistils and leaves collected 3 days after infection (3 DAI) showed profuse hyphal growth in A. lyrata (Additional file 8 : Figure S3) as well as in A. thaliana and A. halleri [ 20 ]. For both control and treatments, pistils or leaves from three biological replicates were collected, each replicate containing equivalent amounts of material from 4 individual plants.…”
Section: Resultsmentioning
confidence: 99%
“…For example, DEFL SCRs are involved in self-incompatibility [ 18 ], while LUREs, another DEFL subgroup, are secreted by ovules to attract competent pollen tubes of their own species during pollination [ 19 ]. Many DEFLs of these and other subgroups are differentially expressed also in the immune responses to Fusarium graminearum [ 20 ]. Similarly, the Capsicum annum defensin CADEF1 is expressed in response to both biotic and abiotic stresses [ 21 ] while antimicrobial PDF1s form Arabidopsis thaliana more closely related to DEFLs that confer heavy metal tolerance in Arabidopsis halleri [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity between the stigma-pollen interaction and plant-pathogen interaction has been discussed and has drawn researchers’ attention for a long time 10,4244 . Several transcriptomic analyses of pollinated stigmas/pistils reported enrichment in transcripts linked to stress or defense response in female tissues 18,20,33,44,45 . Tung et al and Leydon et al suggested that such defense-related genes would have function in pollination.…”
Section: Discussionmentioning
confidence: 99%
“…Tung et al and Leydon et al suggested that such defense-related genes would have function in pollination. Moreover, the incompatible response has been considered to share common mechanism with plant-pathogen interaction as it is a response to block the invader 18,44 . However, in our analysis, GO terms associated with defense responses did not clearly appear after incompatible pollination but rather were mainly represented in compatible response (Fig.…”
Section: Discussionmentioning
confidence: 99%